Cellular and Molecular Mechanisms of Chronic Kidney Disease with Diabetes Mellitus and Cardiovascular Diseases as Its Comorbidities - Gajjala, Prathibha Reddy; Sanati, Maryam; Jankowski, Joachim (Frontiers in Immunology, 2015)
Chronic kidney disease (CKD), diabetes mellitus (DM) and cardiovascular diseases (CVD) are complex disorders of partly unknown genesis and mostly known progression factors. CVD and DM are the risk factors of CKD and are strongly intertwined since DM can lead to both CKD and/or CVD and CVD can lead to kidney disease. In recent years our knowledge of CKD, DM and CVD has been expanded and several important experimental, clinical and epi-demiological associations have been reported. The tight cellular and molecular interactions between the renal, diabetic and cardiovascular systems in acute or chronic disease settings is becoming increasingly evident. However, the (patho-) physiological basis of the interactions of CKD, DM and CVD with involvement of multiple endogenous and environmental factors is highly complex and our knowledge still at its infancy. Not only single pathways and media-tors of progression of these diseases have to be considered in these processes, but also the mutual interactions of these factors are essential. The recent advances in proteomics and inte-grative analysis technologies have allowed rapid progress in analyzing complex disorders and clearly show the opportunity for new efficient and specific therapies. More than a dozen pathways have been identified so far, including hyperactivity of the renin-angiotensin-aldosterone system, osmotic sodium retention, endothelial dysfunction, dyslipidemia, RAS/RAF/ERK pathway, modification of the purinergic system, phosphatidylinositol 3-kinase (PI 3-kinase)-dependent signaling pathways, andinflammation, all leading to histomor-phological alterations of the kidney and vessels of diabetic and non-diabetic patients. Since a better understanding of the common cellular and molecular mechanisms of these diseases may be a key to successful identification of new therapeutic targets, we review in this paper the current literature about cellular and molecular mechanisms of CKD.